English courseware for preschool student - Nurul Mahaya, Abdul Razak (2012)
This paper presents a project related to the interactive multimedia (IMM) courseware for preschool students using user adaptive technique (AUI) and decision making technique. The purpose of this project is to develop the English courseware for preschool students and to implement the above two techniques in the multimedia courseware. The targeted users of this software are 6 years old students and English language is chose as the subject based on the curriculum standard by Malaysian Government. An adaptive user interface technique (AUI) let the students to choose their preferred preferences of the interfaces such as the layouts, the cursor, and the characters of the narrators. Besides, decision making technique that implement in the courseware will assist the students to make their decision. The courseware is developed based on ADDIE methodology. It is hoped that the development of this courseware could attract students towards learning activities and as well as enhancing preschool English language education specifically in Malaysia.